If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (b + -4)(b + -4) = 0 Reorder the terms: (-4 + b)(b + -4) = 0 Reorder the terms: (-4 + b)(-4 + b) = 0 Multiply (-4 + b) * (-4 + b) (-4(-4 + b) + b(-4 + b)) = 0 ((-4 * -4 + b * -4) + b(-4 + b)) = 0 ((16 + -4b) + b(-4 + b)) = 0 (16 + -4b + (-4 * b + b * b)) = 0 (16 + -4b + (-4b + b2)) = 0 Combine like terms: -4b + -4b = -8b (16 + -8b + b2) = 0 Solving 16 + -8b + b2 = 0 Solving for variable 'b'. Factor a trinomial. (4 + -1b)(4 + -1b) = 0Subproblem 1
Set the factor '(4 + -1b)' equal to zero and attempt to solve: Simplifying 4 + -1b = 0 Solving 4 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1b = 0 + -4 -1b = 0 + -4 Combine like terms: 0 + -4 = -4 -1b = -4 Divide each side by '-1'. b = 4 Simplifying b = 4Subproblem 2
Set the factor '(4 + -1b)' equal to zero and attempt to solve: Simplifying 4 + -1b = 0 Solving 4 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1b = 0 + -4 -1b = 0 + -4 Combine like terms: 0 + -4 = -4 -1b = -4 Divide each side by '-1'. b = 4 Simplifying b = 4Solution
b = {4, 4}
| 3x+2y=15solvey | | -6x+1+7x=-8+13 | | f(x)=ln(81sin^2(x)) | | 3n+2.8=6.7 | | 0.09x-0.021x-21002=322 | | -2x+4y-4=0 | | 412x-32-5x=31x+42 | | 3/17 | | 2L+21L-52=94 | | 4+5*67+67=67(1+56*67) | | 55+3y-8=180 | | 6(x-3)=3(3x-5) | | 2x-4+x=-5x+x*5 | | -4(2x+4)-7=-19 | | 5(x+2)=5(3x+2) | | 5x^2-63x+72=0 | | (6-x)(4-x)=0 | | x(12-2x)(8-2x)=0 | | x^2+xy-2y^2+x-11y-12=0 | | 3c+14=5c | | 21x/52 | | 6x+8=10x-4 | | X-18/2=5X | | 4a+2e=70 | | r^2-12+w+3wr-4tr= | | 4d^-4e^-1/2f^-4 | | 2x^3-5x^2-12x+27=0 | | 4x-5-2x=13 | | 5/8-2/4= | | 4/7a=14 | | 15-1/3x=14 | | 12-81= |